2021
DOI: 10.1093/jxb/erab038
|View full text |Cite
|
Sign up to set email alerts
|

Phytochromes control metabolic flux, and their action at the seedling stage determines adult plant biomass

Abstract: Phytochrome (phy) photoreceptors are known to regulate plastic growth responses to vegetation shade. However, recent reports also suggest an important role for phys in carbon resource management, metabolism, and growth. Here, we use 13CO2 labelling patterns in multi-allele phy mutants to investigate the role of phy in the control of metabolic fluxes. We also combine quantitative data of 13C incorporation into protein and cell wall polymers, gas exchange measurements and system modelling to investigate why biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
(104 reference statements)
1
5
0
Order By: Relevance
“…A transient increase in TCA cycle-related gene expression during supplementary FR illumination was also observed in our pathway analysis. This also concurs with previous metabolite analysis in Arabidopsis which revealed higher levels of TCA intermediates in response to shade (Yang et al, 2016;Krahmer et al, 2021). However, again, this alteration was not observed to persist in our assay 2 h beyond the removal of the FR illumination.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A transient increase in TCA cycle-related gene expression during supplementary FR illumination was also observed in our pathway analysis. This also concurs with previous metabolite analysis in Arabidopsis which revealed higher levels of TCA intermediates in response to shade (Yang et al, 2016;Krahmer et al, 2021). However, again, this alteration was not observed to persist in our assay 2 h beyond the removal of the FR illumination.…”
Section: Discussionsupporting
confidence: 93%
“…The most dramatic enrichment was seen among upregulated genes associated with major carbohydrate metabolism. The shade avoidance response is known to cause significant changes in metabolism and recent metabolic analyses have also shown that phytochrome modulates the balance between starch and sugar metabolism in Arabidopsis Krahmer et al., 2021 ). This is particularly significant given the key involvement of alteration of sugar metabolism in the cold acclimation response ( Tarkowski and Van den Ende, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The first days of life are critical for plant survival; successful seedling establishment relies on the mobilisation of seed reserves and the perception of light through wavelength-specific photoreceptors to support emergence before the switch to photo-autotrophic growth. HEXOKINASE 1 (HXK1), a metabolic enzyme with glucose-sensor signalling properties, and PHYTOCHROME-INTERACTING FACTORS (PIFs), play a pivotal role in coupling carbon availability to growth in the developing seedling (Rolland et al, 2002, Moore et al, 2003, Stewart et al, 2011, Lilley et al, 2012, Sairanen et al, 2013, de Wit et al, 2018, Krahmer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Both phy and PIFs have been implicated in carbon resource partitioning, where they have an important role in adjusting growth allocations to sink tissues in darkness and shaded conditions (Yang et al, 2016, de Wit et al, 2018, Krahmer et al, 2021). PIFs are involved sucrose regulation of hypocotyl growth; the pifQ mutant is insensitive to sucrose supplementation, and PIF5 protein stability is moderated by sucrose.…”
Section: Introductionmentioning
confidence: 99%
“…Growth plasticity is a fundamental property of plants, enabling adjustment to changes in the environment. The shade-avoidance syndrome (SAS) is a well-known adaptive response to the presence of nearby vegetation that is characterized by gross changes in plant architecture and biomass ( 1 3 ). A common feature of SAS is the reduction in leaf blade growth, which can be dramatic in heavy vegetation shade.…”
mentioning
confidence: 99%